A Review of Quality Models for Evaluating Quality in Open Source Software - Chauhan, Harvinder; Ganpati, Anita; Singh, Hardeep (International Journal of Computer Sciences and Engineering, 2025)
Open source software (OSS) projects are available in various application domains in a large number. It is difficult to choose any product/project. Quality is a big concern while choosing a software among many of the same type. To measure the quality there are many quality models around us since long. More specifically, from 2003 ,there has been many quality models available in OSS. But how good these quality models are ,remains the question of concern. This research is intended to provide an insight in existing quality models and provide the strength & weakness of these models, thus to provide the OSS community a best suitable quality model. In this paper, the researchers have reviewed the available literature on some conventional quality models and some selective OSS quality models, and carried out a comparative study on these models. In first generation models, open source maturity model embraces the maximum quality characteristics. We concluded that Qual-OSS quality model in second generation is close to international standard organization (ISO) 25010 quality standard. The second generation models offer more tools to support the quality evaluation by considering the community characteristic of OSS.